Desain sepatu kasual pria dengan teknologi 3D printing - Choirul Anam; Tri Andhika (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2021)
Shoes is a mat or footwear that is usually made of leather, Indonesia's footwear industry is included in the top 5 ranking as world exporters. With the 4.0 industrial revolution, Indonesia is expected to be able to keep abreast of industry developments and compete. The way to keep abreast of industry developments is by applying technology, one of which is 3D printing. In addition to being a strategy in the face of the industrial revolution, the application of 3D printing in shoe designs has its own advantages when compared to conventional ways of using leather materials, such as enabling the process of designing and making shoes easier, faster, and customable. Therefore, shoe designs are needed using 3D printing. In the design process, used a qualitative research method approach with analysis to produce a design. Case studies through comparative studies of previous similar product research. Analysis of 3D printing and shoe requirements, as well as design analysis. The resulting synthesis is the product printed with 3D printing on the upper part separately. Using standard out sol that have size 42. With direct print 3D printing applying an auxetic pattern using PLA filaments.